Roles of digital marketing communications over conventional marketing: a perspective on Ogilvy & Mather Communications (Pvt.) Ltd - Hasan, Md. Fuad (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.